Treatment strategies for osteochondral lesions of the talus: A review of the recent evidence. (June 2021) - Qulaghassi, Mahdi; Cho, Young Seok; Khwaja, Murtaza; Dhinsa, Baljinder
Highlights: 28 studies were used for data extraction. Total of 1061 patients total. Strategies were broadly divided into: repair, regeneration and replacement. Microfracture was the most used first line treatment, with or without supplementation. Regeneration and replacement treatments are reserved as second line therapies. Microfracture seems to be effective especially for lesions less than 1.5 cm² in size. Level I evidence remains limited. Abstract: Background: There has been no consensus regarding the treatment of osteochondral lesions of the talus, there has been many attempts to formulate a treatment pathway, with multiple proposed modalities and adjuncts used. Objectives: The aim of this paper was to investigate the evidence published in the recent history, identify the relevant papers, review and summarize the findings, to help clarify the available operative treatment options and their respective efficacies based on the level of evidence provided. Study design & methods: A literature search through electronic databases MEDLINE and EMBASE was done, these databases were screened for publications and papers form June 2004 to June 2019. Key words were utilised in the search 'talus, talar, tibia, cartilage, osteochondral, ankle, osteochondritis dissecans, articular cartilage'. Studies on adults aged 18–60 years were included. Exclusion criteria were studies with less than 10 patients, or no clear outcome was recorded. Papers were reviewed by the authors and data extracted as per a pre-defined proforma. Results: Following screening, 28 published articles were included and reviewed. Of these publications 5 were level I, 7 level II, 4 level III and 12 level IV. The total number of patients was 1061 patients. Treatment modalities included arthroscopic microfracture, drilling, hyaluronic acid injection, platelet rich plasma, osteochondral autologous transplantation (OAT), vascularised free bone graft among others. The most common functional measures used to assess efficacy were the Visual analogue scale (VAS) and the American Orthopaedic Foot and Ankle (AOFAS) score. Follow up ranged from 26 weeks upto 4 years. Conclusions: Despite the abundance of treatment options, high level evidence (level I) remains limited and does not conclude a definitive treatment modality as superior to others. Further research, in the form highly organised randomised clinical trials, is needed to help improve the efficacy and develop new treatment modalities in the future.